The Influence Of Spiritual Intelligence And Lifestyle On The Management Of Students' Personal Finances - Serlina Senansa Senora; Nur Ida Iriani; Moh. Askiyanto (International Research & Development for Human Beings (IRDH), 2025)
The aim of this research is to determine the influence of spiritual intelligence and lifestyle on personal financial management of UNITRI Management students class of 2021, both partially and simultaneously. This type of quantitative research, the research population came from UNITRI Management students class of 2021 totaling 246 people, the sampling technique used cluster (area) random sampling so that 72 people were obtained, the instrument used a questionnaire, data analysis used multiple linear regression analysis, hypothesis testing used the t test (partial ) and F test (simultaneous). The results of multiple linear regression showed that both independent variables had positive regression coefficient values. The results of multiple linear regression analysis also obtained a coefficient of determination R Square of 0.588 (the contribution of the independent variable to the dependent variable was 58.8%). The results of the t-test hypothesis testing (partial) showed that the three independent variables had tcount > ttable values ​​with significance < 0.05 and the results of F hypothesis testing (simultaneous) showed Fcount > Ftable values ​​with significance < 0.05. So it is concluded that spiritual intelligence and lifestyle have a significant influence on the personal financial management of UNITRI Management students class of 2021, both partially and simultaneously. Based on these findings, students are advised to apply spiritual principles, such as simplicity, responsibility and gratitude, in their daily lifestyle.